2012
DOI: 10.1186/1472-6882-12-220
|View full text |Cite
|
Sign up to set email alerts
|

Piper betle shows antioxidant activities, inhibits MCF-7 cell proliferation and increases activities of catalase and superoxide dismutase

Abstract: BackgroundBreast cancer is the most common form of cancer and the focus on finding chemotherapeutic agents have recently shifted to natural products. Piper betle is a medicinal plant with various biological activities. However, not much data is available on the anti-cancer effects of P. betle on breast cancer. Due to the current interest in the potential effects of antioxidants from natural products in breast cancer treatment, we investigated the antioxidant activities of the leaves of P. betle and its inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 48 publications
5
55
0
5
Order By: Relevance
“…Also, in the assessment of the antioxidant capacities of garlic extracts, the ethyl acetate extract showed the highest ferric reducing and radical scavenging activities (1). In addition, the antioxidant activity can be related to other bioactive compounds such as dietary fibers, microelements (especially Se) and polyphenols (17).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the assessment of the antioxidant capacities of garlic extracts, the ethyl acetate extract showed the highest ferric reducing and radical scavenging activities (1). In addition, the antioxidant activity can be related to other bioactive compounds such as dietary fibers, microelements (especially Se) and polyphenols (17).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that SOD enhancing constituents of Brassica rapa L. are more distributed in aqueous and ethyl acetate fraction. Elegant work from Abrahim and contributors (32) showed that ethyl acetate is the most optimal solvent for the extraction of compounds with antioxidant and anti-proliferative activities. Moreover, Mahdy and colleagues (33) which examined SOD from erythrocytes of the Alzheimer' disease induced rats, showed an elevation of the value and further ameliorates the neurodegeneration characteristic of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Due to their ROS-scavenging and antioxidative action, plant phenols have a dosedependent inhibition on the growth and proliferation of cancer cells. 9,10 One of the most important strategies in the treatment of obesity includes inhibitors of nutrient digestion in an attempt to reduce energy intake through pancreatic lipase and amylase inhibition. 11,12 The lipase hydrolyzes a molecule of triglyceride in position 1 and 3, releasing fatty acid and 2-monoglyceride.…”
Section: Introductionmentioning
confidence: 99%